Psychosocial Impact of Acne Vulgaris, its prevalence and associated Risk Factors in University Students of Rawalpindi/ Islamabad - Shahzad, Asima; Mashhadi, Syed Fawad; Zia, Aiman; Masood, Maryam; Ashfaq, Namaan; Khan, Najm us Saqib (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To determine the prevalence of Acne Vulgaris, its effects on quality of life of the patient and its associated risk factors. Study Design: Analytical Quantitative cross-sectional study. Place and Duration of Study: University of Rawalpindi/Islamabad Pakistan, from Mar to May 2021. Methodology: Non-probability convenience sampling was used. A total sample of 218 diagnosed cases of acne was included in our study. The data was collected via online Google forms and analyzed using SPSS 25.0. Results: The prevalence of acne vulgaris was 16.8% in university students of Rawalpindi/Islamabad Pakistan. Among 218 acne cases, the overall Dermatology Life Quality Index score showed 36(17%) cases had no effect at all and 182(83%) had some effect on their quality of life. The impaired quality of life was associated with education and family history (p<0.05). Relatively more impaired aspects of life were physical symptoms (67%), one’s own perception of acne (68%) and interference with work/studies (60%). Conclusion: The impact of acne on physical symptoms and self-confidence of people affected their mental health. As a result, these patients found difficulties in studies, work, and their social life. Knowledge about one’s ailment, early access to treatment and improved compliance significantly improves one’s quality of life. Acne is a deeply rooted issue with serious psychological and social implications which need to be addressed.